The Dynamics of Meranao Political Participation in Southern Philippines: An Analysis Using Milbrath’s Hierarchy of Political Involvement - Jamel Rombo Cayamodin (Insaniyat : Journal of Islam and Humanities, 2021)
The study analyzes the dynamics of political participation of the largest Muslim ethnolinguistic group in the Philippines – the Meranao. Using Milbrath’s hierarchy of political involvement, the researcher examines the nature of Meranaos’ political processes and the role played by demographic and socioeconomic factors including gender, place of origin, age, income, education, and occupation on the nature of their political participation. The study adopted quantitative approach whereby survey method is the primary technique during the collection of data. There were 315 respondents who took part in the five-month survey period in the two districts of the province of Lanao del Sur in Southern Philippines. The research question is summed up on how do Meranaos participate in Philippine politics vis-a-vis Milbrath’s Hierarchy of Political Involvement, and how do social stratification in the Meranao society influence their political participation. The study found that the nature of Meranaos’ political participation is not up to democratic setup as they are confined only to spectatorial level, while rarely participating in transitional and gladiatorial levels. In the same manner, there were no significant impacts of demographic and socioeconomic factors on political participation. The effects were only found in individual formative items at a lesser extent. The study recommends the massive information drive on the status and significant roles of political institutions in the Meranao society in order to entice higher political participation. Extension of this study to other Muslim ethnolinguistic groups and communities in the Philippines is essential.